Regenerated cellulose fiber material as well as preparation method and application thereof
By using aprotic co-solvent and polyaramide to form a composite spinning liquid in the preparation of regenerated cellulose fibers, the strength and fibrillation problems of regenerated cellulose fibers are solved, and the fiber performance of high-strength and low fibrillation is achieved.
Patent Information
- Application Number
- CN202510035712.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The dry/wet strength and fibrillation degree of existing regenerated cellulose fibers are not ideal, resulting in poor performance of fabrics in terms of dimensional stability and wear resistance.
The cellulose pulp is swelled by aprotic and polar aid solvent, and the polyaramide solution is added to the cellulose solution to form a polyaramide/cellulose composite spinning liquid. The polyaramide/cellulose composite fiber is prepared by dry-spray wet spinning process, and is subjected to post-treatment such as drafting, oiling and drying to improve the fiber performance.
The dry/wet strength of the regenerated cellulose fiber is significantly improved and the fibrillation degree is reduced, which improves the mechanical properties of the fibers and the dimensional stability and wear resistance of the fabric.
Smart Images

Figure CN119800537A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of regenerated cellulose, and more specifically to a regenerated cellulose fiber material and a preparation method and application thereof. Background Art
[0002] Regenerated cellulose fiber is made by dissolving natural cellulose (such as wood pulp and cotton linters) in a specific solvent to form a polymer solution, and then regenerating these polymer solutions into the desired solid fiber form through various fiber spinning technologies. Regenerated cellulose fiber has the characteristics of good hygroscopicity, comfort and excellent spinnability. It is often blended with cotton, wool or various synthetic fibers for various types of clothing and decorative textiles. The traditional wet spinning process for preparing viscose fiber is being replaced by new environmentally friendly cellulose dissolving systems, such as ionic liquids, sodium hydroxide (NaOH) / urea / thiourea systems or N-methylmorpholine-N-oxide (NMMO) solvents, due to the problem of severe environmental pollution. The technical research and process development of green, environmentally friendly and high-strength regenerated cellulose fibers have significant social and economic benefits, and are conducive to promoting the sustainable development and product upgrading of my country's chemical fiber industry.
[0003] Currently, the production of sustainable, high-performance fabrics requires single (short) fibers to have high dry / wet strength. Although the inexpensive NaOH / urea / thiourea system can quickly dissolve cellulose and obtain new cellulose composite fibers through wet spinning, the strength problems of the fibers prepared by it (especially the wet strength is usually only about half of the dry strength) often lead to poor performance of fabrics prepared from such cellulose fibers in terms of dimensional stability and wear resistance. As solvents for cellulose, ionic liquids and NMMO are crucial to control viscosity during the spinning process: too high viscosity will affect the fluidity of the spinning solution, resulting in spinning difficulties, which in turn affects the formation and performance of the fiber; too low temperature will cause the spinning solution to have too high viscosity; too high temperature will cause cellulose degradation. In addition, lyocell fibers usually have a high tendency to fibrillate under conditions of moisture, swelling or high mechanical wear, which limits their application in the field of textiles and clothing.
[0004] Therefore, under the premise of ensuring the toughness of regenerated cellulose fibers, efficiently improving the dry / wet strength of fibers and reducing the degree of fiber fibrillation is a common technical challenge both in the field of scientific research and in production practice. Summary of the invention
[0005] The present invention provides a regenerated cellulose fiber material and a preparation method and application thereof, which are used to solve the problem that the dry / wet strength and fibrillation degree of the regenerated cellulose in the prior art are not ideal.
[0006] In a first aspect, the present invention provides a method for preparing a regenerated cellulose fiber material, comprising the following steps: adding a co-solvent to cellulose pulp for swelling, and then adding it to a dissolving system, stirring and dissolving to obtain a cellulose solution; wherein the co-solvent is a non-protonic, polar solvent; adding a polyaramid solution to the cellulose solution under high-speed stirring conditions to form a polyaramid / cellulose composite spinning solution; passing the polyaramid / cellulose composite spinning solution through a spinning device and then spinning it into a deionized water coagulation bath to obtain polyaramid / cellulose composite fibers; and performing post-treatment operations on the polyaramid / cellulose composite fibers to obtain the regenerated cellulose fiber material.
[0007] As a possible implementation, the mass ratio of the cellulose pulp, the co-solvent and the dissolving system is 1:8-12:8-12; and / or the solid content of the cellulose solution is 4 wt%-10 wt%;
[0008] And / or, the mass ratio of the polyaramid solution to the cellulose solution is 1:19-99; and / or, the swelling time is 50-70 min; and / or, the stirring and dissolving conditions are: temperature 70-90° C., time 200-300 min.
[0009] As a possible implementation, the post-processing operation includes the following steps: sequentially performing stretching, oiling, and drying operations on the polyaramid / cellulose composite fiber to obtain the regenerated cellulose fiber material.
[0010] As a possible implementation, the polyaromatic amide is any one of heterocyclic aromatic polyamide, poly(p-phenylene terephthalamide), poly(p-phenylene terephthalamide) and poly(m-phenylene isophthalamide); and / or the cosolvent is any one of 1,3-dimethyl-2-imidazolidinone, N,N-dimethylformamide, dimethyl sulfoxide, dimethylformamide, acetonitrile and hexamethylphosphoric triamide; and / or the dissolving system is any one of 1-butyl-3-methylimidazolium chloride, N-methylmorpholine-N-oxide, imidazole-type ionic liquid, quaternary ammonium-type ionic liquid, pyrrolidine-type ionic liquid, piperidine-type ionic liquid and N-methylmorpholine-N-oxide.
[0011] As a possible implementation method, the preparation process of the heterocyclic aromatic polyamide includes the following steps: adding p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole and terephthaloyl chloride to a dimethylacetamide / lithium chloride solution in a molar ratio of 1:1:2 to obtain a solution of the heterocyclic aromatic polyamide.
[0012] In a second aspect, the present invention provides a regenerated cellulose fiber material prepared by the preparation method described in any possible implementation of the first aspect.
[0013] As a possible implementation method, its wet strength is 60.27~79.38 MPa, and its dry strength is 192.32~218.06 MPa, and its strength will be further improved in industrial production.
[0014] In a third aspect, the present invention provides an application of a regenerated cellulose fiber material prepared by the preparation method described in any possible implementation of the first aspect or a regenerated cellulose fiber material described in any possible implementation of the second aspect in the field of textiles and clothing and / or sanitary materials.
[0015] As a possible implementation method, the regenerated cellulose fiber material is blended with natural fibers and synthetic fibers for use in textiles.
[0016] As a possible implementation, the natural fibers include but are not limited to cotton, wool, linen, and bamboo fibers; and / or the synthetic fibers include but are not limited to polyester, spandex, and nylon.
[0017] As a possible implementation manner, the textile is used for clothing or decoration.
[0018] The decisive factors for the mechanical properties of regenerated cellulose fiber are the purity of pulp, the solid content of spinning solution or the added reinforcing components. If the solid content of spinning solution is too high, the viscosity of spinning solution will increase, which is not conducive to spinning process. In the scheme of regenerated cellulose fiber with reinforcing components added, due to the extremely strong hydrogen bonding between cellulose molecular chains, it is difficult for the reinforcing components to form a homogeneous system with cellulose, so most processes simultaneously introduce a cross-linking system to avoid phase separation between components. The technical solution provided by the present invention introduces an aramid system to enhance regenerated cellulose fiber. Both molecular chains have extremely strong hydrogen bonding, and it is easy to form a homogeneous system. Moreover, due to the recombination of hydrogen bonds, the mechanical properties of regenerated cellulose fiber are significantly improved, and the degree of fibrillation is greatly reduced. In the ionic liquid system or NMMO system, the viscosity of spinning solution is very large. Although high temperature can reduce the viscosity of spinning solution, it will cause degradation of cellulose; and the addition of non-protonic polar solvent can effectively reduce the viscosity of spinning solution, which is beneficial to the spinning process.
[0019] The present invention provides a regenerated cellulose fiber material (taking heterocyclic aromatic polyamide as an example), in which a polyaromatic polyamide solution is uniformly mixed with a cellulose solution in different proportions in an ionic liquid system (taking 1-butyl-3-methylimidazolium chloride as an example) to form a polyaromatic polyamide / cellulose composite spinning solution, and the polyaromatic polyamide / cellulose composite fiber is prepared by a dry-jet wet spinning process, after being spun by a spinning device, entering a deionized water coagulation bath, and the polyaromatic polyamide / cellulose composite fiber is stretched, oiled and dried to obtain a regenerated cellulose fiber material. The added reinforcing component polyaramid has the characteristics of high strength and high modulus. When added to the regenerated cellulose fiber, it can improve the mechanical properties and reduce the degree of fibrillation; and polyaramid can play the role of reinforcing the skeleton in the regenerated cellulose fiber, and can withstand greater tensile force and pressure, thereby improving the strength and modulus of the fiber; further, the amide groups on the polyaramid molecular chain and the hydroxyl groups on the regenerated cellulose fiber molecular chain can form more intermolecular hydrogen bonds and there are mass transfer differences, realizing the cross-linked interpenetrating network structure of the molecular chains inside the fiber, increasing the bonding force between the fibers, significantly improving the mechanical strength and toughness of the fiber, and significantly reducing the degree of fibrillation. At the same time, the regenerated cellulose fiber material provided by the present invention reduces the apparent viscosity of the cellulose spinning solution due to the introduction of a non-protonic polar solvent (a cosolvent such as 1,3-dimethyl-2-imidazolidinone), ensuring the smooth processing of the spinning solution, is simple and easy, low cost, highly repeatable, has a significant reinforcing effect, and has the potential for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 The morphologies of heterocyclic aromatic polyamide / cellulose composite spinning solution-A1, heterocyclic aromatic polyamide / cellulose composite spinning solution-A2 and heterocyclic aromatic polyamide / cellulose composite spinning solution-A3 provided in the embodiments of the present invention, wherein a is cellulose solution-D, b is heterocyclic aromatic polyamide / cellulose composite spinning solution-A1, c is heterocyclic aromatic polyamide / cellulose composite spinning solution-A2, and d is heterocyclic aromatic polyamide / cellulose composite spinning solution-A3.
[0022] Figure 2 The results of quantification and comparison of the tensile breaking strength (wet strength) and tensile breaking strength (dry strength) of the regenerated cellulose fiber material-D and each regenerated cellulose composite fiber provided in the embodiment of the present invention.
[0023] Figure 3 This is an apparent morphology diagram of the heterocyclic aromatic polyamide / cellulose composite fiber-A2 provided in an embodiment of the present invention, wherein a is the fiber macroscopic morphology, b is the single fiber strength-elongation relationship curve, c is the fiber surface morphology under a scanning electron microscope, and d is the fiber cross-sectional morphology under a scanning electron microscope.
[0024] Figure 4 Optical microscope images of the heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A2 and the regenerated cellulose fiber material-D provided in the embodiments of the present invention, wherein a, b, c are regenerated cellulose fiber material-D, and d, e, f are heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A2. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In order to solve the problem that the dry / wet strength and fibrillation degree of regenerated cellulose in the prior art are not ideal, an embodiment of the present invention provides an experimental method for preparing a regenerated cellulose fiber material.
[0027] A cosolvent (aprotic, polar solvent) is added to cellulose pulp for swelling, and then added to a dissolving system, stirred and dissolved to obtain a cellulose solution; a polyaramid solution is added to the cellulose solution under high-speed stirring conditions to form a polyaramid / cellulose composite spinning solution; the polyaramid / cellulose composite spinning solution is spun through a spinning device and then enters a deionized water coagulation bath to obtain a polyaramid / cellulose composite fiber; and the polyaramid / cellulose composite fiber is post-treated to obtain a regenerated cellulose fiber material.
[0028] In the present invention, the mass ratio of cellulose pulp, co-solvent and dissolving system is 1:8~12:8~12; and / or, the solid content of cellulose solution is 4 wt%~10 wt%; the mass ratio of polyaramid solution and cellulose solution is 1:19~99; the swelling time is 50~70 min; the stirring dissolution conditions are: temperature 70~90°C, time 200~300 min. The polyaromatic amide is any one of heterocyclic aromatic polyamide, poly(p-phenylene terephthalamide), poly(p-phenylene terephthalamide) and poly(m-phenylene isophthalamide); the cosolvent is any one of 1,3-dimethyl-2-imidazolidinone, N,N-dimethylformamide, dimethyl sulfoxide, dimethylformamide, acetonitrile and hexamethylphosphoric triamide; and the dissolving system is any one of 1-butyl-3-methylimidazolium chloride, N-methylmorpholine-N-oxide, imidazole-type ionic liquid, quaternary ammonium-type ionic liquid, pyrrolidine-type ionic liquid, piperidine-type ionic liquid and N-methylmorpholine-N-oxide.
[0029] The technical solutions of the present invention under the above conditions can obtain the target product, and the fiber toughness, dry / wet strength and fibrillation degree of the target product are qualified and can achieve ideal effects.
[0030] In the examples provided by the present invention, the preparation conditions of product A1, product A2 and product A3 are taken as examples for characterization and testing. It is proved that the regenerated cellulose fiber material provided by the present invention has good orientation, and the cross section is uniform and has no defects; the regenerated cellulose fiber material provided by the present invention has excellent tensile breaking strength and qualified fracture toughness; the regenerated cellulose fiber material provided by the present invention has excellent mechanical properties and significantly lower fibrillation degree.
[0031] The technical solution of the present invention will be further described below in conjunction with specific embodiments.
[0032] Example 1
[0033] This example provides an experiment for preparing a regenerated cellulose fiber material.
[0034] Preparation of product A1, product A2 and product A3: p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole and terephthaloyl chloride were added to dimethylacetamide / lithium chloride (DMAc / LiCl) solution at a molar ratio of 1:1:2, the temperature was controlled at 30°C, and the reaction was carried out for 4 hours to obtain a solution of heterocyclic aromatic polyamide with a solid content of 5%-A. 10 g of cellulose pulp was added to 95 g of 1,3-dimethyl-2-imidazolidinone and swelled for 1 hour, and then 95 g of 1-butyl-3-methylimidazolium chloride was added, and the mixture was stirred and dissolved at 80°C for 4 hours to obtain a cellulose solution with a solid content of 5 wt%-A. The heterocyclic aromatic polyamide solution-A was added to the cellulose solution-A at a mass ratio of 1:99, 2:98, and 3:97 under stirring at a speed of 1000 rpm to obtain heterocyclic aromatic polyamide / cellulose composite spinning solution-A1, heterocyclic aromatic polyamide / cellulose composite spinning solution-A2, and heterocyclic aromatic polyamide / cellulose composite spinning solution-A3. The heterocyclic aromatic polyamide / cellulose composite spinning solution-A1, heterocyclic aromatic polyamide / cellulose composite spinning solution-A2, and heterocyclic aromatic polyamide / cellulose composite spinning solution-A3 were respectively spun through a spinning device and then entered into a deionized water coagulation bath to obtain heterocyclic aromatic polyamide / cellulose composite fiber-A1, heterocyclic aromatic polyamide / cellulose composite fiber-A2, and heterocyclic aromatic polyamide / cellulose composite fiber-A3. Heterocyclic aromatic polyamide / cellulose composite fiber-A1, heterocyclic aromatic polyamide / cellulose composite fiber-A2 and heterocyclic aromatic polyamide / cellulose composite fiber-A3 are respectively stretched, oiled and dried in sequence to obtain heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A1, heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A2 and heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A3.
[0035] Preparation of product B: m-phenylenediamine and isophthaloyl chloride were added to DMAc / LiCl solution at a molar ratio of 1:1, the temperature was controlled at 30°C, and the reaction was carried out for 4 h to obtain a poly(m-phenylene isophthalamide) solution-B with a solid content of 5%. 5 g of cellulose pulp, 86 g of NMMO and 9 g of water were mixed and stirred and dissolved at 90°C for 4 h to obtain a cellulose solution-B with a solid content of 5 wt%. The poly(m-phenylene isophthalamide) solution-B was added to the cellulose solution-B at a mass ratio of 2:98 under stirring conditions at a speed of 1000 rpm to obtain a poly(m-phenylene isophthalamide) / cellulose composite spinning solution-B. The poly(m-phenylene terephthalamide) / cellulose composite spinning solution-B was spun through a spinning device and successively entered into a coagulation bath of 30 wt% and 10 wt% NMMO aqueous solution to obtain a poly(m-phenylene isophthalamide) / cellulose composite fiber-B. The poly(m-phenylene isophthalamide) / cellulose composite fiber-B is sequentially stretched, oiled, and dried to obtain the poly(m-phenylene isophthalamide) reinforced regenerated cellulose fiber material-B.
[0036] Preparation of product C: m-phenylenediamine and isophthaloyl chloride were added to DMAc / LiCl solution at a molar ratio of 1:1, the temperature was controlled at 30°C, and the reaction was carried out for 4 h to obtain a solution-C of heterocyclic aromatic polyamide with a solid content of 5%. 10 g of cellulose pulp was added to 95 g of 1,3-dimethyl-2-imidazolidinone and swelled for 1 h, and then 95 g of 1-butyl-3-methylimidazolium chloride was added and dissolved at 80°C with stirring for 4 h to obtain a cellulose solution-C with a solid content of 5 wt%. The cellulose solution-C was spun through a spinning device and then entered into a deionized water coagulation bath to obtain a cellulose composite fiber-C, which was sequentially drawn, oiled, and dried to obtain a regenerated cellulose fiber material-C. The heterocyclic aromatic polyamide solution-C was coated on the surface of the regenerated cellulose fiber material-C, rinsed with water for 10 min for solvent exchange, and then dried to obtain a heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-C.
[0037] Preparation of product D: 5 g of cellulose pulp was added to 95 g of 1-butyl-3-methylimidazolium chloride, and the mixture was stirred and dissolved at 80°C for 4 h to obtain a cellulose solution D with a solid content of 5 wt%. The cellulose solution D was spun through a spinning device and then entered into a deionized water coagulation bath to obtain a cellulose composite fiber D, which was then sequentially drawn, oiled, and dried to obtain a regenerated cellulose fiber material D.
[0038] Example 2
[0039] This embodiment provides a performance characterization experiment of a regenerated cellulose fiber material.
[0040] Rheological characterization of spinning solution: A digital viscometer (SNB-2, China) was used to test the composite spinning solution. 50 mL of the spinning solution was taken into a beaker and measured at 80 °C using an L4 rotor. The measurement unit is mPa·s.
[0041] Characterization of single fiber mechanical properties: The mechanical properties of the regenerated cellulose composite fibers were tested using an electronic single yarn strength tester (YM061, China). The clamp distance was set to 30 mm, the tensile speed was fixed at 10 mm / min, and each sample was measured 5 times to take the average value. The wet and dry strength (MPa), elongation at break (%) and work at break (cN·mm) were calculated and recorded.
[0042] Fiber morphology characterization: Scanning electron microscopy (FEI Quanta 200, USA) was used to test the surface and cross-sectional micromorphology of the regenerated cellulose composite fibers. Liquid nitrogen brittle fracture treatment was used for the complete sample preparation of the fiber cross section.
[0043] Anti-fibrillation performance characterization: The regenerated cellulose fiber material to be tested was evaluated using an optical microscope, and the fibrillation index was calculated (the calculation formula is as follows: I f = ; Where: I f The regenerated cellulose fiber material to be tested was cut into small pieces of about 2 cm in length, added into deionized water and mixed to prepare a fiber slurry with a concentration of 0.1%. The slurry was then treated in an ultrasonic cell disruptor at 500 W for 30 min and 60 min, and the fibrillation performance was evaluated by optical microscope images.
[0044] In this embodiment, the heterocyclic aromatic polyamide / cellulose composite spinning solution-A1, heterocyclic aromatic polyamide / cellulose composite spinning solution-A2, heterocyclic aromatic polyamide / cellulose composite spinning solution-A3, poly(m-phenylene isophthalamide) / cellulose composite spinning solution-B, heterocyclic aromatic polyamide solution-C and cellulose solution-D of embodiment 1 are used as composite spinning solutions to be tested; the heterocyclic aromatic polyamide / cellulose composite fiber-A1, heterocyclic aromatic polyamide / cellulose composite fiber-A2, heterocyclic aromatic polyamide / cellulose composite fiber-A3, poly(m-phenylene isophthalamide) / cellulose composite spinning solution-B, heterocyclic aromatic polyamide solution-C and cellulose solution-D of embodiment 1 are used as composite spinning solutions to be tested; / Cellulose composite fiber-B, cellulose composite fiber-C and cellulose composite fiber-D were respectively used as the regenerated cellulose composite fibers to be tested; the heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A1, heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A2, heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A3, polyisophthalamide-m-phenylenediamine reinforced regenerated cellulose fiber material-B, heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-C and regenerated cellulose fiber material-D of Example 1 were respectively used as the regenerated cellulose fiber materials to be tested, and the results were as shown in Tables 1 and Figure 1~Figure 4 Results shown.
[0045] Table 1 Performance characterization results of regenerated cellulose fiber materials
[0046]
[0047] The morphologies of cellulose solution-D, heterocyclic aromatic polyamide / cellulose composite spinning solution-A1, heterocyclic aromatic polyamide / cellulose composite spinning solution-A2 and heterocyclic aromatic polyamide / cellulose composite spinning solution-A3 are shown in FIG. Figure 1 As shown, it can be seen that the regenerated cellulose spinning solutions with different proportions of heterocyclic aromatic polyamide all have good spinnability. As the proportion of heterocyclic aromatic polyamide increases, the apparent viscosity of the spinning solution decreases, which is conducive to spinning.
[0048] The morphology of the heterocyclic aromatic polyamide / cellulose composite fiber-A1 in Example 1 was observed by scanning electron microscopy, and the following was obtained: Figure 3 The results shown. Figure 3 It can be clearly seen that the fibers have good orientation and the cross section is uniform and has no defects, which is beneficial to the improvement of the mechanical properties of the fibers.
[0049] From Table 1 and Figure 2It can be seen that the heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A1, heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A2 and heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A3 (nascent fiber) prepared in Example 1 of the present invention have a tensile breaking strength (wet strength) of 60.27~79.38 MPa, and the breaking strength (wet strength) of the regenerated cellulose fiber material-D (nascent fiber) is 54.39 MPa; the heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A1, heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A2, heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A3 (nascent fiber) have a tensile breaking strength (dry strength) of 192.32~218.06 MPa, and the breaking strength (dry strength) of the regenerated cellulose fiber material-D (nascent fiber) is 154.16 Mpa; the corresponding elongations at break are 200.07%~222.21% respectively, the latter is 219.88%; compared with the regenerated cellulose fiber material-D, the work of fracture is improved, and the prepared fibers have qualified toughness.
[0050] Optical microscope images of heterocyclic aromatic polyamide reinforced regenerated cellulose fiber material-A2 and regenerated cellulose fiber material-D are shown in FIG. Figure 4 As shown by Figure 4 It can be seen that after the fibrillation treatment, the surface of heterocyclic aromatic polyamide / cellulose composite fiber-A2 is smooth and no fine fibrils appear; while the fibrillation index of regenerated cellulose fiber material-D is 0, 0.1, and 0.2 with the increase of treatment time, and the fibrillation becomes more serious. It can be seen that the reinforcing component heterocyclic aromatic polyamide added in this scheme forms more intermolecular hydrogen bonds with the regenerated cellulose, realizing the cross-linked interpenetrating network structure of the molecular chain inside the fiber, improving the mechanical properties of the fiber, and reducing the degree of fibrillation.
[0051] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0052] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a regenerated cellulose fiber material, characterized in that: The following steps are involved: Adding a co-solvent to cellulose pulp for swelling, then adding it to a dissolving system, stirring and dissolving, to obtain a cellulose solution; wherein the co-solvent is a non-protonic, polar solvent; adding the polyaramid solution to the cellulose solution under high-speed stirring to form a polyaramid / cellulose composite spinning solution; The polyaramid / cellulose composite spinning solution is spun through a spinning device and then enters a deionized water coagulation bath to obtain polyaramid / cellulose composite fibers; The polyaramid / cellulose composite fiber is subjected to post-treatment operation to obtain the regenerated cellulose fiber material.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the cellulose pulp, the co-solvent and the dissolving system is 1:8-12:8-12; and / or, the solid content of the cellulose solution is 4 wt% to 10 wt%; And / or, the mass ratio of the polyaramid solution to the cellulose solution is 1:19-99; And / or, the swelling time is 50 to 70 min; And / or, the stirring and dissolving conditions are: temperature 70-90° C., time 200-300 min.
3. The preparation method according to claim 1, characterized in that: The post-processing operation comprises the following steps: The polyaramid / cellulose composite fiber is sequentially subjected to drawing, oiling and drying operations to obtain the regenerated cellulose fiber material.
4. The preparation method according to claim 1, characterized in that: The polyaromatic amide is any one of heterocyclic aromatic polyamide, poly(p-phenylene terephthalamide), poly(p-phenylene terephthalamide) and poly(m-phenylene isophthalamide); and / or, the cosolvent is any one of 1,3-dimethyl-2-imidazolidinone, N,N-dimethylformamide, dimethyl sulfoxide, dimethylformamide, acetonitrile and hexamethylphosphoric triamide; And / or, the dissolving system is any one of 1-butyl-3-methylimidazolium chloride, N-methylmorpholine-N-oxide, imidazole-type ionic liquid, quaternary ammonium-type ionic liquid, pyrrolidine-type ionic liquid, piperidine-type ionic liquid and N-methylmorpholine-N-oxide.
5. The preparation method according to claim 4, characterized in that: The preparation process of the heterocyclic aromatic polyamide comprises the following steps: p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole and terephthaloyl chloride are added to the dimethylacetamide / lithium chloride solution at a molar ratio of 1:1:2 to obtain a solution of the heterocyclic aromatic polyamide.
6. The regenerated cellulose fiber material prepared by the preparation method according to any one of claims 1 to 5.
7. The regenerated cellulose fiber material according to claim 6, characterized in that Its wet strength is 60.27~79.38MPa, and its dry strength is 192.32~218.06MPa.
8. Use of the regenerated cellulose fiber material prepared by the preparation method according to any one of claims 1 to 5 or the regenerated cellulose fiber material according to any one of claims 6 to 7 in the field of textiles and clothing and / or sanitary materials.
9. The use according to claim 8, characterized in that: The regenerated cellulose fiber material is blended with natural fibers and synthetic fibers for use in textiles.
10. The use according to claim 9, characterized in that: The natural fibers include but are not limited to cotton, wool, linen, and bamboo fibers; and / or, the synthetic fibers include but are not limited to polyester, spandex, and nylon; And / or, the textile is used for clothing or decoration.
Citation Information
Patent Citations
Semi-continuous preparation method for solution of heterocycle-containing aromatic polyamide copolymer
CN101985497A
Chlorine-containing high-performance heterocyclic aromatic polyamide fiber and preparation method thereof
CN107779975A
Nanometer aramid fiber reinforced regenerated cellulose fiber material, preparation method and application
CN114507910A